REGISTROS POLÍNICOS DE DEPÓSITOS DEL HOLOCENO EN EL SUDESTE DE PATAGONIA, ARGENTINA: SU APLICACIÓN EN LA RECONSTRUCCIÓN PALEOAMBIENTAL (Ameghiniana, 2014)
This work presents the pollen analysis of deposits from southeastern Patagonia (Argentina) aimed to reconstruct changes in vegetation and environmental conditions and its relationship to huntergatherer groups who inhabited the area. Pollen sequences from an archeological site (cave Cóndor 1) and an eolian-colluvial deposit with a pedogenesis process in the upper section corresponding to the late Holocene were analyzed. There is a change at the base of the sequence,from an Ephedra-dominated steppe to a grass-dominated steppe, indicating an increase in water availability. Both a lower humidity and a rise in temperature are suggested by increasing bushes during the early Holocene. The lack of pollen between 3250 and c. 1200 cal. yr BP maybe related to the intensity of human activities. Pollen assemblages dated between c. 1050 and 600 cal. yr BP, suggest conditions in the area were drier than at present. Establishment a grass-dominated steppe and a soil layer at c. 600 cal. yr BP suggest more stable environmentalconditions and an increased hydric availability. Increased erosion rates over the past few centuries produced an eolian deposit overlaying the soil, coeval with the European settlement.